Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.